The Split Distance 2 Domination in Graphs - Lakshmi, A.; Ameenal Bibi, K.; Jothilakshmi, R. (International Journal of Engineering and Technology, 2018)
A distance - 2 dominating set DÂ V of a graph G is a split distance - 2 dominating set if the induced sub graph <V-D> is disconnected. The split distance - 2 domination numberÂ is the minimum cardinality of a split distance - 2 dominating set. In this paper, we defined the notion of split distance - 2 domination in graph. We got many bounds on distance - 2 split domination number. Exact values of this new parameter are obtained for some standard graphs. Nordhaus - Gaddum type results are also obtained for this new parameter.Â Â